PREPARATION AND CHARACTERIZATION OF ETODOLAC BEARING EMULSOMES - GILL, VIVEK; NANDA, ARUN (International Journal of Applied Pharmaceutics, 2020)
Objective: Emulsomes are novel vesicular drug delivery system with an internal solid lipid core surrounded by one or more bilayers of phospholipids. Etodolac is a potent anti-inflammatory drug and is a drug of choice for the treatment of various diseases. The present study is focused on the development of emulsomes using etodolac as drug candidates having improved drug loading with sustained-release effect for patient compliance. Methods: Emulsomes formulation composed of solid lipids (tristearin), phospholipids, cholesterol, stearylamine, and drug (etodolac) were prepared by lipid film hydration method followed by sonication to produce emulsomes of the nanometric size range. All the formulations were optimized by using box-behnken design of experiment considering 3 factors viz. drug to phospholipid ratio (A), tristearin to phospholipid ratio (B), stearylamine to phospholipid ratio (C) at 3 levels lower (-1), middle (0) and upper (+1). The response of the independent variables (A, B, C) was studied on the dependent variable viz. particle size (Y1), zeta potential (Y2), and entrapment efficiency (Y3). The responses were analyzed by design expert software to find out the optimized values of variables within the design space. Results: Compatibility with excipients was established by FTIR studies. The developed emulsomes were spherical shape vesicles as analyzed by TEM. The optimized batch (OB) was evaluated for particle size, zeta potential, and entrapment efficiency with experimental values 383.1 ± 11.7 nm, 47.2 ± 1.3 mV and 80.1 ± 3.2% and predicted values 390.394 nm, 45.000 mV and 81.642 %, respectively. The experimental values were found in reasonable agreement with predicted values by the design of the experiment. In vitro drug release study showed sustained release of the drug (88.69 % after 24 h). Conclusion: Etodolac loaded emulsomes is a novel drug delivery system and found to reliable in terms of various characteristic parameters like particle size, zeta potential, entrapment efficiency, and drug release. 3-factors 3-levels Box-behnken design of the experiment is a suitable design for the optimization of emulsomes.